2009
DOI: 10.1002/ddrr.51
|View full text |Cite
|
Sign up to set email alerts
|

Mathematics deficiencies in children with very low birth weight or very preterm birth

Abstract: Children with very low birth weight (VLBW, <1500 g) or very preterm birth (VPTB, <32 weeks gestational age or GA) have more mathematics disabilities or deficiencies (MD) and higher rates of mathematics learning disabilities (MLD) than normal birth weight term‐born children (NBW, >2500 g and >36 weeks GA). MD are found even in children without global disorders in cognition or neurosensory status and when IQ is controlled, and they are associated with other learning problems and weaknesses in percept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
88
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 91 publications
(104 citation statements)
references
References 79 publications
14
88
1
1
Order By: Relevance
“…Their deficit in mathematical achievement was of a similar magnitude to previous studies (3) and was not attributed to differences in nonverbal IQ or socioeconomic deprivation. Commensurate with previous studies, this performance was indicative of a specific problem with mathematics rather than simply reflecting a difference in general intelligence or socioeconomic factors (21). Importantly, we have shown that very preterm children did not show evidence of imprecise numerical representations and their poorer performance in specific mathematical tasks was entirely accounted for by their domain-general deficits in working memory and visuospatial skills, but not nonverbal IQ.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Their deficit in mathematical achievement was of a similar magnitude to previous studies (3) and was not attributed to differences in nonverbal IQ or socioeconomic deprivation. Commensurate with previous studies, this performance was indicative of a specific problem with mathematics rather than simply reflecting a difference in general intelligence or socioeconomic factors (21). Importantly, we have shown that very preterm children did not show evidence of imprecise numerical representations and their poorer performance in specific mathematical tasks was entirely accounted for by their domain-general deficits in working memory and visuospatial skills, but not nonverbal IQ.…”
Section: Discussionsupporting
confidence: 87%
“…These general cognitive skills have also been identified as being important for mathematical achievement in typically developing children (4,7). Deficits in visuospatial skills and working memory are frequently reported in preterm samples (21), however, this is the first study to identify that general cognitive deficits can explain group differences in specific mathematical skills, which in turn are known to contribute to more complex mathematical performance (4,7,18).…”
Section: Discussionmentioning
confidence: 82%
“…Literacy skills do not seem to be improving in more contemporary EP/ ELBW cohorts: the group differences and rates of impairment were marginally lower in the VICS 1991-1992 cohort. 2 As reported previously, 2,29,30 concerns were even greater for the EP/ ELBW cohort with regard to arithmetic, as this group scored 0.6 SD below their T/NBW peers. Given the difficulties EP/ ELBW children have acquiring rudimentary academic skills, further research is needed to determine the basis for these learning deficits.…”
Section: Discussionsupporting
confidence: 72%
“…Children born with low birth weight have higher rates of disability in both reading and math (74,85), with math reasoning being more severely affected (85). Very preterm children are more likely to have individual (65%) and multiple (30%) learning disabilities compared with term controls (13% and 3%, respectively) (25).…”
Section: School Achievement/learning Disabilitymentioning
confidence: 99%